The Effect of Information Feedback in Construction Bidding - Alexander Soo; Bee Oo (Construction Economics and Building, 2010)
With the goal to achieve efficiency in bidding competitions, many codes of bidding procedure recommend clients provide contractors with bidding feedback information. Contractors strive to bid competitively via learning based on their experiences in past bidding attempts. The level of bidding feedback information, however, varies across clients. In many cases, clients do not provide feedback or provide insufficient feedback to contractors. Focussing on two information feedback conditions (full and partial), we examine: (i) the changes in bidding trend over time, and (ii) the effects of bidding feedback information on bidders’ competitiveness in bidding. Data were gathered using a bidding experiment that involved student (inexperienced) bidders with a construction project management background. The results show that the variations in bids over time for full information feedback condition are statistically significant, but not for bids from bidders with partial bidding feedback information. Bidders with full bidding feedback information are more competitive than those with partial bidding feedback information. The findings add to both our theoretical and empirical understanding of construction bidding: an understanding of the process of changes in the price of building work, and how the process can be manipulated through the release of bidding feedback information.